Effect of Pinus taeda Hydrolyzed Lignin on Biochemical Profile, Oxidative Status, and Semen Quality of Healthy Dogs - Aiudi, Giulio G.; Cicirelli, Vincenzo; Maggiolino, Aristide; Burgio, Matteo; Bragaglio, Andrea; Tateo, Alessandra; De Palo, Pasquale (Frontiers in Veterinary Science, 2022)
Sub-fertility represents a frequent challenge in canine reproduction. The use of micronutrients and/or additives was investigated as an approach to improve sperm quality, which are the main constraints on reproduction in canine species. Although some information is available about the effect of daily supplementation with substances presenting antioxidant/antioxidative activity on semen quality, this study aimed to observe the effect of a polyphenolic mix of substances derived from hydroxylation of Pinus taeda lignin (PTHL). For the trial, 40 male dogs were involved, 20 received PTHL for 90 days and 20 were left untreated, serving as a control group. Every 30 days, blood and semen samples were collected and analyzed. The biochemical profile of both groups was not affected by treatment and time (p > 0.05). Differently, dogs that received PTHL showed higher blood superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activity (p < 0.01). Moreover, the dietary addition of PTHL can significantly increase the semen volume, concentration, and spermatozoa motility (p < 0.01) in healthy dogs. PTHL supplementation represents a good way to enhance the semen quality of dogs and improve the antioxidant status of animals.